A code of conduct : a treatise on the etiquette of the Fatimid Ismaili mission : a critical edition of the Arabic text and English translation of Aḥmad b. Ibrāhīm al-Naysābūrī's al-Risāla al-mūjaza al-kāfiya fī ādāb al-duʿāt /: a treatise on the etiquette of the Fatimid Ismaili mission : a critical edition of the Arabic text and English translation of Aḥmad b. Ibrāhīm al-Naysābūrī's al-Risāla al-mūjaza al-kāfiya fī ādāb al-duʿāt. (2011) - Unknown
No abstract available